The distribution of constituent words in nominal compounds and its impact on semantic interpretation: an empirical study - Annelen Brunner; Stefan Engelberg; Katrin Hein (Zeitschrift für Wortbildung)
The paper explores factors that influence the distribution of constituent words of compounds over the head and modifier position. The empirical basis for the study is a large database of German compounds, annotated with respect to the morphological structure of the compound and the semantic category of the constituents. The study shows that the polysemy of the constituent word, its constituent family size, and its semantic category account for tendencies of the constituent word to occur in either modifier or head position. Furthermore, the paper explores the degree to which the semantic category combination of head and modifier word, e.g., x=substance and y=artifact, indicates the semantic relation between the constituents, e.g., y_consists_of_x.